Integrating Software Product Line Engineering and Agile Development - Mohan, Kannan; Ramesh, Balasubramaniam; Sugumaran, Vijayan (IEEE software, 2010)
A software product line is a set of software-intensive systems sharing a common, managed set of features, developed from reusable core assets and incorporating variations to derive product variants. This involves identifying commonality and variability in the product family and implementing shared artifacts while preserving the ability to implement required variability. Software development organizations that recognize market opportunities for products that share a significant number of common elements, but that also exhibit variations, can reap significant economic benefits with SPLE. Agile methods emphasize improvisation over conventional development approaches. These methods focus on quick development in an uncertain, ill-understood environment in which requirements rapidly evolve. These methods also view people, rather than formal documentation, as a project's most important element.